The Effect of Tractor Utilization on Revenue and Use of Labor on Rice Farming in Sambas Regency - Adi Suyatno; Imelda Imelda; Komariyati Komariyati (AGRARIS: Journal of Agribusiness and Rural Development Research, 2018)
Development of agriculture mechanization in Sambas Regency is needed in order to support the increased of rice production. Technically, agricultural mechanization is expected to increase the productivity of the land and, economically, it is expected to increase farmers' income. The purpose of this research is to analyze the effect of tractor usage on income and availability of labor in rice farming. This research was conducted in Sambas Regency, using survey method. The results showed that the use of tractors for soil processing significantly increased the productivity and income of rice farming. The use of tractors on soil treatment has increased productivity by 667 kg/ha. The use of tractors on land treatment also increased revenues by Rp.2.843.400,-/ha, although raising the cost. In-house labor and farming families are available for soil cultivation, but farmers generally prefer to use the tractors for soil treatment. The use of tractors has reduced the use of labor, thus accelerating land preparation and planting activities. Farmers who do not use tractors because of environmental factors farming, namely the unavailability of irrigation.